Mitigating Hazards Through Continuing Design: The Birth and Evolution of a Pediatric Intensive Care Unit - Madsen, Peter; Desai, Vinit; Roberts, Karlene; Wong, Daniel (Organization Science, 2006)
Often, researchers study organizations in which design is largely in place and the design process is shrouded in the distant past. However, the design process can have dramatic implications for how organizations function. This paper reports a specific attempt to design one organizational subunit, a pediatric intensive care unit (PICU), to function under difficult circumstances. The founders aimed to create a highly reliable and safe unit, but implementing their vision required continuous effort. The unit needed constant buffering from external pressures and a dissimilar parent organization, and these forces shaped the unit’s ultimate design. Through the presentation of this case, we discuss the impact of design on the organization, its members, and the larger hospital organization to which the unit belonged. The study reveals that the PICU’s design was an ongoing effort and its most stable component was a vision of distributed knowledge and decentralized intensive care. We conclude by discussing implications of the case for organizational design theory and practice.